Carbon-material-containing low-filling high-thermal-conductivity insulating PEI / PPS composite material and preparation method thereof

By using low fill amount and shear dispersion technology of twin screw extruders in PEI/PPS composites, a selectively distributed thermal conductivity and insulation network is formed, which solves the problem of insufficient performance of existing thermal conductivity and achieves both high thermal conductivity, insulation and mechanical properties.

CN119823574APending Publication Date: 2025-04-15SILVER AGE ENG PLASTICS DONGGUAN +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510040029.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing thermally conductive composite materials lead to poor fluidity, low mechanical properties under high filling, and the inability to achieve high thermal conductivity and insulation properties at the same time.

Method used

Using a low-filled PEI/PPS composite material, a composite material with PEI as the dispersed phase and PPS as the continuous phase is formed by the shear dispersed phase of the twin-screw extruder. The carbon material filler is selectively distributed in the PEI phase, and the inorganic thermally conductive filler is selectively distributed in the PPS phase, forming a complete 3D thermally conductive mesh chain and an insulating layer.

Benefits of technology

The thermal conductivity is significantly improved, with a thermal conductivity of 5.1~5.6W/m·K, while maintaining excellent electrical insulation and excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237416530000121
    Figure BDA0005237416530000121
Patent Text Reader

Abstract

The invention belongs to the field of high polymer materials, and particularly relates to a low-filling high-thermal-conductivity insulating PEI / PPS composite material containing a carbon material and a preparation method of the composite material. The preparation method provided by the invention comprises the following steps: a) preparing raw materials, wherein the raw materials comprise PPS, PEI, an inorganic heat-conducting filler, a carbon material filler, an antioxidant and a lubricant; b) carrying out melt blending extrusion, granulation and drying on PEI, the carbon material filler, part of the antioxidant and part of the lubricant at 350-380 DEG C to obtain a carbon material / PEI master batch; and c) carrying out melt blending extrusion on the carbon material / PEI master batch, PPS, inorganic heat-conducting filler, the balance of antioxidant and the balance of lubricant at 280-300 DEG C, granulating and drying to obtain the PEI / PPS composite material. The prepared composite material has good heat conduction and insulation performance, and the excellent mechanical property of the composite material can be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a low-filling, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon materials and a preparation method thereof. Background Art

[0002] In recent years, in the field of electronics and electrical, with the miniaturization, lightweight, intelligence, integration and functionalization of electronic products and the emergence of new applications such as three-dimensional chip stacking architecture, flexible electronic devices and light-emitting diodes, more and more heat is generated per unit volume of the equipment. If the generated heat cannot be conducted away in time, it may cause the operating temperature of the electronic equipment to increase sharply, thus having a serious negative impact on the service life and performance stability of the electronic equipment. Therefore, the research and development of high thermal conductivity insulation materials has become urgent.

[0003] Traditional metal thermal conductive materials have poor chemical corrosion resistance and electrical insulation, and cannot meet their application in certain fields. Inorganic ceramic thermal conductive materials have good insulation, but their processing and molding process requirements are high and their impact resistance is poor. Therefore, the application of traditional thermal conductive materials such as metal materials and inorganic ceramic materials is also limited due to their own limitations.

[0004] Polymer materials are characterized by light weight, low cost, chemical corrosion resistance, easy processing, excellent mechanical properties and electrical insulation, and are widely used in the defense industry and various fields of the national economy. However, most polymer materials are poor conductors of heat. Common polymer materials such as polypropylene, polystyrene, and polycarbonate have low thermal conductivity, mainly in the range of 0.1-0.5W / m·K, which seriously restricts the application of polymer materials in the field of thermal conductive materials. However, adding high thermal conductive fillers is the most commonly used method for preparing thermal conductive composite materials.

[0005] Metal and carbon materials are commonly used thermal conductive fillers. Composite materials with thermal conductivity can be prepared by extrusion granulation. For example, Chinese patent document No. CN 101469109B discloses a polyester / metal fiber conductive, thermally conductive, fast crystallization composite material and its preparation method. When the weight content of metal fiber is 5.7wt%, the thermal conductivity of the PTT / stainless steel fiber composite material is 14W / m·K, and the electrical conductivity can reach 1.0×10 2S / cm. Chinese patent document No. CN 201810728632.8 discloses a highly thermally conductive and electrically conductive graphene composite material and a preparation method thereof. When the graphene content is about 0.05wt%, the thermal conductivity of the graphene / epoxy resin composite material is 27W / m·K and the electrical conductivity is 6S / m. Most of these thermally conductive composite materials have high thermal conductivity, but they have the defect of being non-insulated, which greatly limits their scope of use. It is a common method to use insulating inorganic fillers to prepare thermally conductive and insulating composite materials. Common ones include various metal oxides such as aluminum oxide, magnesium oxide, nitrides such as magnesium nitride, boron nitride, etc., and carbides such as boron carbide, titanium carbide, etc. Chinese patent document No. CN104356490A discloses a thermally conductive and insulating polyolefin composite material and a preparation method thereof. When the BN content is 40wt%, the thermal conductivity of the BN / EVA / PE composite material is 0.6W / m·K and the volume resistivity is 1.24×10 13 Ω·cm. However, this type of thermal conductive material has low thermal conductivity, with an average thermal conductivity of less than 2W / m·k. Composite materials need to be highly filled to achieve thermal conductivity, which will result in poor fluidity and low mechanical properties of the composite materials.

[0006] In order to solve the existing difficulties, researchers have adopted a variety of means to improve the performance of thermally conductive insulating composite materials. Carbon nanotubes have been reported for their high thermal conductivity in thermally conductive insulating composite materials. In particular, at low filling amounts, the thermal conductivity of the composite material is greatly improved and has attracted research attention, but there is still high electrical conductivity. In order to overcome the conductivity problem caused by filling, the use of an insulating layer to coat or reduce its amount to avoid the formation of a conductive network is currently the main technical method. Chinese patent document No. CN201410825948.0 discloses a magnesium oxide nanocrystal-coated graphene composite material and a preparation method thereof, and proposes to use magnesium oxide to coat graphene to improve its insulation, but the thermal conductivity is inevitably reduced. Chinese patent document No. CN 104861298A discloses a thermally conductive insulating composite material of carbon nanotubes and a preparation method thereof, which is composed of the following components by weight: 100 parts of polypropylene, 40 parts of boron nitride, 3.5 parts of treated multi-walled carbon nanotubes, 1.5 parts of a siloxane coupling agent, 10100.4 parts of phenols, and 3.5 parts of paraffin. Then, it is extruded by a twin-screw extruder. After adding multi-walled carbon nanotubes, its thermal conductivity is significantly improved, but the volume resistivity is significantly reduced. In order to maintain the electrical insulation performance of the composite material, the carbon nanotube filling amount can only be kept low, and the high thermal conductivity of carbon nanotubes cannot be maximized.

[0007] Based on the above, although metal and carbon materials can achieve high thermal conductivity of composite materials as thermal conductive fillers, they cannot overcome the defects caused by non-insulation, which greatly limits the application scope of such thermal conductive composite materials; although inorganic thermal conductive fillers can achieve electrical insulation, they have poor thermal conductivity, insufficient processing performance and mechanical properties. Therefore, developing a composite material that can achieve high thermal conductivity, insulation and excellent mechanical properties has become an important research and development direction in this field. Summary of the invention

[0008] In view of this, the purpose of the present invention is to provide a low-filling, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon and a preparation method thereof. The composite material prepared by the present invention has both good thermal conductivity and insulation properties and can ensure the excellent mechanical properties of the composite material.

[0009] The present invention provides a method for preparing a low-filled, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon, comprising the following steps:

[0010] a) preparing raw materials, the raw materials comprising PPS resin, PEI resin, inorganic thermal conductive filler, carbon material filler, antioxidant and lubricant; wherein the PPS resin accounts for 30-60% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the PEI resin accounts for 20-40% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the inorganic thermal conductive filler accounts for 10-30% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the carbon material filler accounts for 1-10% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the antioxidant accounts for 0.1-1% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, and the lubricant accounts for 0.1-1% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler;

[0011] b) mixing the PEI resin, the carbon material filler, part of the antioxidant and part of the lubricant, putting them into a twin-screw extruder, performing melt blending and extrusion at 350-380° C., granulating, and drying to obtain a carbon material / PEI masterbatch;

[0012] c) mixing the carbon material / PEI masterbatch, PPS resin, inorganic thermal conductive filler, the remaining antioxidant and the remaining lubricant, and putting them into a twin-screw extruder, performing melt blending and extrusion at 280-300° C., granulating, and drying to obtain a low-filling, high-thermal conductive insulating PEI / PPS composite material containing carbon material.

[0013] Preferably, the melt index of the PPS resin is 250-450 g / 10 min at a temperature of 316° C. and a load of 2.16 kg.

[0014] Preferably, the melt index of the PEI resin is 8 to 20 g / 10 min at a temperature of 337° C. and a load of 6.6 kg.

[0015] Preferably, the inorganic thermally conductive filler is at least one of boron nitride, silicon nitride, aluminum nitride, silicon carbide, boron carbide, magnesium oxide and aluminum oxide.

[0016] Preferably, the inorganic thermally conductive filler has a shape of at least one of linear, granular and flake.

[0017] Preferably, the linear inorganic thermally conductive filler has a diameter of 20 to 400 nm, a length of 10 to 100 μm, and an aspect ratio of 100 to 1000; the particle size of the granular inorganic thermally conductive filler is 10 nm to 50 μm; the length of the flaky inorganic thermally conductive filler is 200 nm to 100 μm, and the thickness is nanometer level.

[0018] Preferably, the carbon material filler is at least one of carbon nanotubes, graphene, carbon fiber, graphite, amorphous carbon and fullerene.

[0019] Preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 168 and antioxidant B215.

[0020] Preferably, the lubricant is at least one of silicone powder, pentaerythritol and ethylene bis stearamide.

[0021] The present invention provides a low-filling, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon material, which is prepared according to the preparation method described in the above technical solution.

[0022] Compared with the prior art, the present invention provides a low-filling, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon material and a preparation method thereof. The preparation method provided by the present invention comprises the following steps: a) preparing raw materials, the raw materials comprising PPS resin, PEI resin, inorganic thermal conductive filler, carbon material filler, antioxidant and lubricant; wherein the PPS resin accounts for 30-60% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the PEI resin accounts for 20-40% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the inorganic thermal conductive filler accounts for 10-30% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the carbon material filler accounts for 1-10% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the antioxidant accounts for 10% of the total weight of the PPS resin, The invention discloses a method for preparing a carbon material / PEI masterbatch comprising mixing the PEI resin, the inorganic thermal conductive filler and the carbon material filler, wherein the lubricant accounts for 0.1-1% of the total weight of the PEI resin, the inorganic thermal conductive filler and the carbon material filler, and the lubricant accounts for 0.1-1% of the total weight of the PPS resin, the PEI resin, the inorganic thermal conductive filler and the carbon material filler; b) mixing the PEI resin, the carbon material filler, a part of the antioxidant and a part of the lubricant, and putting them into a twin-screw extruder, and performing melt blending and extrusion at 350-380° C., granulating, and drying to obtain a carbon material / PEI masterbatch; c) mixing the carbon material / PEI masterbatch, the PPS resin, the inorganic thermal conductive filler, the remaining antioxidant and the remaining lubricant, and putting them into a twin-screw extruder, and performing melt blending and extrusion at 280-300° C., granulating, and drying to obtain a low-filling, high-thermal conductive insulating PEI / PPS composite material containing carbon material. The present invention adopts "processing temperature control molding technology" to control the temperature of melt blending to make the PPS resin completely melted and only slightly melt the PEI resin. At this time, the PPS melt viscosity is low and the fluidity is good, while the PEI melt viscosity is high and the fluidity is poor. By regulating the morphology of the polymer material during the processing, the thermal conductive filler is selectively distributed, thereby forming a thermal conductive insulating network in the composite material. More specifically, the present invention forms a composite material with PEI as a dispersed phase and PPS as a continuous phase through the shear dispersion effect of a twin-screw extruder. The composite material presents a typical "sea-island" structure. Since the PEI melt viscosity is relatively high and the fluidity is poor at this time, the carbon material filler is "forced" to be selectively distributed in the PEI phase, that is, the carbon material filler cannot penetrate into the PPS phase, and the inorganic thermally conductive filler is "forced" to be selectively distributed in the PPS phase, that is, the inorganic thermally conductive filler cannot penetrate into the PEI phase; the carbon material / PEI phase is like an "island" for heat transfer, and the inorganic thermally conductive filler in the PPS phase is like a "bridge in the sea" for heat transfer. The composite material is prepared in this way to form a complete 3D thermal conductive network chain, and the inorganic thermally conductive filler / PPS phase forms an insulating layer, based on which an excellent high thermal conductivity insulating composite material can be prepared.The experimental results show that the thermal conductivity of the thermally conductive composite material prepared by the present invention is significantly improved, and the thermal conductivity of the obtained thermally conductive composite material is 5.1-5.6 W / m·K; moreover, the composite material also has excellent electrical insulation, and the volume resistivity is greater than 10. 15 Ω·cm; at the same time, the filler filling amount of the composite material is controlled in a relatively low range, ensuring the excellent mechanical properties of the composite material. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The present invention provides a method for preparing a low-filled, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon, comprising the following steps:

[0025] a) preparing raw materials, wherein the raw materials include PPS resin, PEI resin, inorganic thermal conductive filler, carbon material filler, antioxidant and lubricant;

[0026] b) mixing the PEI resin, the carbon material filler, part of the antioxidant and part of the lubricant, putting them into a twin-screw extruder, performing melt blending and extrusion at 350-380° C., granulating, and drying to obtain a carbon material / PEI masterbatch;

[0027] c) mixing the carbon material / PEI masterbatch, PPS resin, inorganic thermal conductive filler, the remaining antioxidant and the remaining lubricant, and putting them into a twin-screw extruder, performing melt blending and extrusion at 280-300° C., granulating, and drying to obtain a low-filling, high-thermal conductive insulating PEI / PPS composite material containing carbon material.

[0028] In the preparation method provided by the present invention, in step a), the PPS resin is preferably a linear polyphenylene sulfide resin; the melting point of the PPS resin is preferably 270-290°C, more preferably 280°C; the melt index of the PPS resin at a temperature of 316°C and a load of 2.16kg is preferably 200-500g / 10min, more preferably 250-450g / 10min.

[0029] In the preparation method provided by the present invention, in step a), based on the total weight percentage of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler as 100%, the content of the PPS resin is 30-60wt%, specifically 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59wt% or 60wt%.

[0030] In the preparation method provided by the present invention, in step a), the PPS resin is preferably dried before use; the drying method is preferably vacuum drying; the drying temperature is preferably 100-150°C, specifically 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C; the drying time is preferably 4-12h, specifically 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h.

[0031] In the preparation method provided by the present invention, in step a), the melt index of the PEI resin at a temperature of 337° C. and a load of 6.6 kg is preferably 5 to 25 g / 10 min, more preferably 8 to 20 g / 10 min.

[0032] In the preparation method provided by the present invention, in step a), in step a), taking the total weight percentage of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler as 100% as a benchmark, the content of the PEI resin is 20-40wt%, specifically 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt% or 40wt%.

[0033] In the preparation method provided by the present invention, in step a), the PEI resin is preferably dried before use; the drying method is preferably vacuum drying; the drying temperature is preferably 100-150°C, specifically 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C; the drying time is preferably 4-12h, specifically 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h.

[0034] In the preparation method provided by the present invention, in step a), the inorganic thermally conductive filler is preferably at least one of boron nitride, silicon nitride, aluminum nitride, silicon carbide, boron carbide, magnesium oxide and aluminum oxide. In the present invention, the shape of the inorganic thermally conductive filler is preferably at least one of linear, granular and flaky; wherein the diameter of the linear inorganic thermally conductive filler is preferably 20-400nm, the length is preferably 10-100μm, and the aspect ratio is preferably 100-1000; the particle size of the granular inorganic thermally conductive filler is preferably 10nm-50μm, specifically 10μm; the length of the flaky inorganic thermally conductive filler is preferably 200nm-100μm, and the thickness is preferably nanometer level.

[0035] In the preparation method provided by the present invention, in step a), taking the total weight percentage of the PPS resin, PEI resin, inorganic thermally conductive filler and carbon material filler as 100% as a benchmark, the content of the inorganic thermally conductive filler is 10-30wt%, specifically 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt% or 30wt%.

[0036] In the preparation method provided by the present invention, in step a), the inorganic thermally conductive filler is preferably dried before use; the drying method is preferably vacuum drying; the drying temperature is preferably 100-150°C, specifically 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C; the drying time is preferably 4-12h, specifically 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h.

[0037] In the preparation method provided by the present invention, in step a), the carbon material filler is preferably at least one of carbon nanotubes, graphene, carbon fiber, graphite, amorphous carbon and fullerene; wherein the carbon nanotubes are preferably single-walled carbon nanotubes and / or multi-walled carbon nanotubes, and the single-walled carbon nanotubes are preferably surface-acidified single-walled carbon nanotubes; the specific surface area of ​​the carbon nanotubes is preferably 50 to 250 m 2 / g, more preferably 100 to 200 m 2 / g; the graphene is preferably graphene oxide; the thickness of the graphene is preferably less than 7.5nm, more preferably less than 6.7nm; the number of carbon atom layers of the graphene is preferably 1 to 30 layers, more preferably 1 to 20 layers.

[0038] In the preparation method provided by the present invention, in step a), taking the total weight percentage of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler as 100% as a benchmark, the content of the carbon material filler is 1 to 10wt%, specifically 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt% or 10wt%.

[0039] In the preparation method provided by the present invention, in step a), the carbon material filler is preferably dried before use; the drying method is preferably vacuum drying; the drying temperature is preferably 100-150°C, specifically 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C; the drying time is preferably 4-12h, specifically 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h.

[0040] In the preparation method provided by the present invention, in step a), the antioxidant is preferably at least one of antioxidant 1010, antioxidant 168 and antioxidant B215.

[0041] In the preparation method provided by the present invention, in step a), based on the total weight percentage of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler as 100%, the content of the antioxidant in the raw material is 0.1-1wt%, specifically 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt%, 0.55wt%, 0.6wt%, 0.65wt%, 0.7wt%, 0.75wt%, 0.8wt%, 0.85wt%, 0.9wt%, 0.95wt% or 1wt%.

[0042] In the preparation method provided by the present invention, in step a), the lubricant is preferably at least one of silicone powder, pentaerythritol and ethylene bis stearamide.

[0043] In the preparation method provided by the present invention, in step a), taking the total weight percentage of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler as 100% as a benchmark, the content of the lubricant in the raw material is 0.1-1wt%, specifically 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt%, 0.55wt%, 0.6wt%, 0.65wt%, 0.7wt%, 0.75wt%, 0.8wt%, 0.85wt%, 0.9wt%, 0.95wt% or 1wt%.

[0044] In the preparation method provided by the present invention, in step b), the amount of the partial antioxidant preferably accounts for 15-40wt% of the total amount of the antioxidant, specifically 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt% or 40wt%.

[0045] In the preparation method provided by the present invention, in step b), the amount of the partial lubricant preferably accounts for 15 to 40 wt% of the total amount of the lubricant, specifically 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt%, 36 wt%, 37 wt%, 38 wt%, 39 wt% or 40 wt%.

[0046] In the preparation method provided by the present invention, in step b), the temperature of the melt blending extrusion can be specifically 350°C, 355°C, 360°C, 365°C, 370°C, 375°C or 380°C.

[0047] In the preparation method provided by the present invention, in step c), the temperature of the melt blending extrusion can specifically be 280°C, 285°C, 290°C, 295°C or 300°C.

[0048] The present invention also provides a low-filling, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon material, which is prepared according to the preparation method described in the above technical solution.

[0049] The technical solution provided by the present invention adopts "processing temperature control molding technology" to control the temperature of melt blending to make the PPS resin completely melted and only slightly melt the PEI resin. At this time, the PPS melt viscosity is low and the fluidity is good, while the PEI melt viscosity is high and the fluidity is poor. By regulating the morphology of the polymer material during the processing, the thermal conductive filler is selectively distributed, thereby forming a thermal conductive insulating network in the composite material. More specifically, the present invention forms a composite material with PEI as the dispersed phase and PPS as the continuous phase through the shear dispersion effect of the twin-screw extruder. The composite material presents a typical "sea-island" structure. Since the PEI melt viscosity is high and the fluidity is poor at this time, the carbon material filler is "forced" to be selectively distributed in the PEI phase, that is, the carbon material filler cannot penetrate into the PPS phase, and the inorganic thermal conductive filler is "forced" to be selectively distributed in the PPS phase, that is, the inorganic thermal conductive filler cannot penetrate into the PEI phase; the carbon material / PEI phase is like an "island" for heat transfer, and the inorganic thermal conductive filler in the PPS phase is like a "bridge in the sea" for heat transfer. The composite material is prepared in this way to form a complete 3D thermal conductive network chain, and the inorganic thermal conductive filler / PPS phase forms an insulating layer, based on which an excellent high thermal conductivity insulating composite material can be prepared. The experimental results show that the thermal conductivity of the thermal conductive composite material prepared by the present invention is significantly improved, and the thermal conductivity of the obtained thermal conductive composite material is 5.1~5.6W / m·K; and the composite material also has excellent electrical insulation, with a volume resistivity greater than 10 15Ω·cm; at the same time, the filler filling amount of the composite material is controlled in a relatively low range, ensuring the excellent mechanical properties of the composite material.

[0050] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.

[0051] Example 1

[0052] A method for preparing a low-filled, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon materials, comprising the following steps:

[0053] (1) PEI resin (melt index 8-20 g / 10 min@337°C / 6.6 kg), PPS resin (linear, melting point 280°C, melt index 250-450 g / 10 min@316°C / 2.16 kg), BN (boron nitride, average particle size 10 μm) and multi-walled carbon nanotubes (specific surface area 100-200 m 2 / g) was dried under vacuum at 120° C. for 8 hours;

[0054] (2) Taking the total weight percentage of multi-walled carbon nanotubes and PEI resin as 100% as a benchmark, 10% of multi-walled carbon nanotubes, 90% of PEI resin, 0.1% of pentaerythritol and 0.1% of antioxidant 1010 were stirred in a high-speed mixer for 0.5 hours, and then the mixed raw materials were put into a twin-screw extruder, melt-blended and extruded at 350-370° C., granulated, and dried to obtain multi-walled carbon nanotube / PEI masterbatch;

[0055] (3) Taking the total weight percentage of multi-walled carbon nanotube / PEI masterbatch (excluding pentaerythritol and antioxidant 1010 contained therein), PPS resin and BN as 100% as a benchmark, 30% of multi-walled carbon nanotube / PEI masterbatch, 40% of PPS resin, 30% of BN, 0.1% of pentaerythritol and 0.1% of antioxidant 1010 were stirred in a high-speed mixer for 0.5 hour, and then the mixed raw materials were put into a twin-screw extruder, melt-blended and extruded at 280-300° C., granulated and dried to obtain a finished thermally conductive insulating composite material.

[0056] Example 2

[0057] A method for preparing a low-filled, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon materials, comprising the following steps:

[0058] (1) PEI resin (melt index 8-20 g / 10 min@337°C / 6.6 kg), PPS resin (linear, melting point 280°C, melt index 250-450 g / 10 min@316°C / 2.16 kg), BN (average particle size 10 μm) and graphene oxide (thickness less than 6.7 nm, 1-20 layers of carbon atoms) were vacuum dried at 120°C for 8 hours;

[0059] (2) Taking the total weight percentage of graphene and PEI resin as 100% as a benchmark, 15% of graphene, 85% of PEI resin, 0.1% of pentaerythritol and 0.1% of antioxidant 1010 were stirred in a high-speed mixer for 0.5 hours, and then the mixed raw materials were put into a twin-screw extruder, melt-blended and extruded at 350-370° C., granulated, and dried to obtain graphene / PEI masterbatch;

[0060] (3) Taking the total weight percentage of graphene / PEI masterbatch (excluding pentaerythritol and antioxidant 1010 contained therein), PPS resin and BN as 100% as a benchmark, 30% of graphene / PEI masterbatch, 40% of PPS resin, 30% of BN, 0.1% of pentaerythritol and 0.1% of antioxidant 1010 were stirred in a high-speed mixer for 0.5 hour, and then the mixed raw materials were put into a twin-screw extruder, melt-blended and extruded at 280-300° C., granulated and dried to obtain a finished thermally conductive insulating composite material.

[0061] Example 3

[0062] A method for preparing a low-filled, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon materials, comprising the following steps:

[0063] (1) PEI resin (melt index 8-20 g / 10 min@337°C / 6.6 kg), PPS resin (linear, melting point 280°C, melt index 250-450 g / 10 min@316°C / 2.16 kg), Al2O3 (aluminum oxide, average particle size 10 μm) and multi-walled carbon nanotubes (specific surface area 100-200 m 2 / g) was dried under vacuum at 120° C. for 8 hours;

[0064] (2) Taking the total weight percentage of multi-walled carbon nanotubes and PEI resin as 100% as a benchmark, 10% of multi-walled carbon nanotubes, 90% of PEI resin, 0.1% of pentaerythritol and 1680.1% of antioxidant were stirred in a high-speed mixer for 0.5 hours, and then the mixed raw materials were put into a twin-screw extruder, melt-blended and extruded at 350-370° C., granulated, and dried to obtain multi-walled carbon nanotube / PEI masterbatch;

[0065] (3) Taking the total weight percentage of multi-walled carbon nanotubes / PEI masterbatch (excluding pentaerythritol and antioxidant 168 contained therein), PPS resin and BN as 100% as a benchmark, 30% of multi-walled carbon nanotubes / PEI masterbatch, 50% of PPS resin, 20% of Al2O3, 0.1% of pentaerythritol and 0.1% of antioxidant 168 were stirred in a high-speed mixer for 0.5 hour, and then the mixed raw materials were put into a twin-screw extruder, melt-blended and extruded at 280-300°C, granulated and dried to obtain a finished thermally conductive insulating composite material.

[0066] Example 4

[0067] A method for preparing a low-filled, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon materials, comprising the following steps:

[0068] (1) PEI resin (melt index 8-20 g / 10 min@337°C / 6.6 kg), PPS resin (linear, melting point 280°C, melt index 250-450 g / 10 min@316°C / 2.16 kg), BN (average particle size 10 μm) and surface acidified single-walled carbon nanotubes (specific surface area 100-200 m 2 / g) was dried under vacuum at 120° C. for 8 hours;

[0069] (2) Taking the total weight percentage of single-walled carbon nanotubes and PEI resin as 100% as a benchmark, 10% of single-walled carbon nanotubes, 90% of PEI resin, 0.1% of pentaerythritol and 0.1% of antioxidant 1010 were stirred in a high-speed mixer for 0.5 hours, and then the mixed raw materials were put into a twin-screw extruder, melt-blended and extruded at 350-370° C., granulated, and dried to obtain single-walled carbon nanotube / PEI masterbatch;

[0070] (3) Taking the total weight percentage of single-walled carbon nanotube / PEI masterbatch (excluding pentaerythritol and antioxidant 1010 contained therein), PPS resin and BN as 100% as a benchmark, 30% of single-walled carbon nanotube / PEI masterbatch, 40% of PPS resin, 30% of BN, 0.1% of pentaerythritol and 0.1% of antioxidant 1010 were stirred in a high-speed mixer for 0.5 hour, and then the mixed raw materials were put into a twin-screw extruder, melt-blended and extruded at 280-300°C, granulated and dried to obtain a finished thermally conductive insulating composite material.

[0071] Comparative Example 1

[0072] A method for preparing a composite material, which differs from the embodiment mainly in that no carbon material filler is added, comprises the following steps:

[0073] (1) PEI resin (melt index 8-20 g / 10 min@337°C / 6.6 kg), PPS resin (linear, melting point 280°C, melt index 250-450 g / 10 min@316°C / 2.16 kg), and BN (average particle size 10 μm) were vacuum dried at 120°C for 8 hours;

[0074] (2) Taking the total weight percentage of PEI resin, PPS resin and BN as 100% as a basis, 70% of BN, 10% of PEI resin, 20% of PPS resin, 0.1% of pentaerythritol and 0.1% of antioxidant 1010 were stirred in a high-speed mixer for 0.5 hour, and then the mixed raw materials were put into a twin-screw extruder, melt-blended and extruded at 350-370°C, granulated and dried to obtain a finished composite material.

[0075] Comparative Example 2

[0076] A method for preparing a composite material, which is mainly different from the embodiment in that one-step melt blending is adopted, and comprises the following steps:

[0077] (1) PEI resin (melt index 8-20 g / 10 min@337°C / 6.6 kg), PPS resin (linear, melting point 280°C, melt index 250-450 g / 10 min@316°C / 2.16 kg), BN (average particle size 10 μm) and multi-walled carbon nanotubes (specific surface area 100-200 m 2 / g) was dried under vacuum at 120° C. for 8 hours;

[0078] (2) Taking the total weight percentage of PEI resin, PPS resin, BN and multi-walled carbon nanotubes as 100% as a benchmark, 3% of multi-walled carbon nanotubes, 30% of BN, 27% of PEI resin, 40% of PPS resin, 0.1% of pentaerythritol and 0.1% of antioxidant 1010 were stirred in a high-speed mixer for 0.5 hour, and then the mixed raw materials were put into a twin-screw extruder, melt-blended and extruded at 350-370° C., granulated and dried to obtain a finished thermal conductive insulating composite material.

[0079] Performance Testing

[0080] The performance of the finished composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 was tested, and the results are shown in Table 1:

[0081] Table 1 Performance test results of finished composite materials

[0082]

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a low-filled, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon, characterized in that: The following steps are involved: a) preparing raw materials, the raw materials comprising PPS resin, PEI resin, inorganic thermal conductive filler, carbon material filler, antioxidant and lubricant; wherein the PPS resin accounts for 30-60% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the PEI resin accounts for 20-40% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the inorganic thermal conductive filler accounts for 10-30% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the carbon material filler accounts for 1-10% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, the antioxidant accounts for 0.1-1% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler, and the lubricant accounts for 0.1-1% of the total weight of the PPS resin, PEI resin, inorganic thermal conductive filler and carbon material filler; b) mixing the PEI resin, the carbon material filler, part of the antioxidant and part of the lubricant, putting them into a twin-screw extruder, performing melt blending and extrusion at 350-380° C., granulating, and drying to obtain a carbon material / PEI masterbatch; c) mixing the carbon material / PEI masterbatch, PPS resin, inorganic thermal conductive filler, the remaining antioxidant and the remaining lubricant, and putting them into a twin-screw extruder, performing melt blending and extrusion at 280-300° C., granulating, and drying to obtain a low-filling, high-thermal conductive insulating PEI / PPS composite material containing carbon material.

2. The preparation method according to claim 1, characterized in that: The melt index of the PPS resin is 250-450 g / 10 min at a temperature of 316° C. and a load of 2.16 kg.

3. The preparation method according to claim 1, characterized in that: The melt index of the PEI resin is 8-20 g / 10 min at a temperature of 337° C. and a load of 6.6 kg.

4. The preparation method according to claim 1, characterized in that: The inorganic thermal conductive filler is at least one of boron nitride, silicon nitride, aluminum nitride, silicon carbide, boron carbide, magnesium oxide and aluminum oxide.

5. The preparation method according to claim 1, characterized in that: The inorganic thermally conductive filler has a shape of at least one of a linear shape, a granular shape, and a flake shape.

6. The preparation method according to claim 5, characterized in that: The linear inorganic thermal conductive filler has a diameter of 20 to 400 nm, a length of 10 to 100 μm, and an aspect ratio of 100 to 1000; the particle size of the granular inorganic thermal conductive filler is 10 nm to 50 μm; the length of the sheet-like inorganic thermal conductive filler is 200 nm to 100 μm, and the thickness is nanometer level.

7. The preparation method according to claim 1, characterized in that: The carbon material filler is at least one of carbon nanotubes, graphene, carbon fibers, graphite, amorphous carbon and fullerene.

8. The preparation method according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010, antioxidant 168 and antioxidant B215.

9. The preparation method according to claim 1, characterized in that: The lubricant is at least one of silicone powder, pentaerythritol and ethylene bis stearamide.

10. A low-filled, high-thermal-conductivity, insulating PEI / PPS composite material containing carbon, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Polyester / metal fibre conductive, heat conducting and fast crystallization composite material and preparation thereof

    CN101469109B

  • Heat conducting insulating polyolefin composite material and preparation method thereof

    CN104356490A

  • A kind of magnesium oxide nanocrystal coated graphene composite material and preparation method thereof

    CN104591233B

  • Heat-conducting and insulated composite material based on carbon nanotubes and preparation method for composite material

    CN104861298A

  • A graphene-based composite material with high thermal conductivity and high electrical conductivity and its preparation method

    CN108929521B